Collaborative Governance in Tourism Development Policy - Ade Ferry Afrisal (Journal of Social Science, 2022)
The tourism sector has an important role in economic development by utilizing its potential and developing new tourism. This tourism development effort is implemented by the government in collaboration with the public in deciding the policies to be implemented or can be called collaborative governance. This study aims to determine the implementation of collaborative governance in tourism development policies. This study uses qualitative research methods, while the data collection techniques are carried out by exploring journals, books and other information relevant to the study. The results show that the government implements collaborative governance in tourism development policies by issuing a number of tour packages to support the development of tourism activities themselves. These activities include promotions, tourist destinations, main and supporting facilities, tourism products and human resources. Due to the collaboration between the government and the community, currently there are various tourist objects that have been known to foreign countries and tourism objects that are in the process of promotion which of course have their respective potentials and attractions.